Challenges of Madrasah Organizational Culture in Promoting Autonomy and Creativity of Islamic Education Teachers in the Implementation of the Merdeka Curriculum - Aqila Kamalia; Irawan Irawan; Chyril Futuhana Ahmad (Al-Ulum: Jurnal Pendidikan Islam, 2026)
School organizational culture influences the success of the Merdeka Curriculum, but bureaucratic and hierarchical cultures often hinder teacher autonomy and creativity. This study aims to analyze school organizational strategies, their implications for teacher autonomy and creativity, and educational strategies that support the implementation of the Merdeka Curriculum. The method used is a literature study, which includes reading various journals, academic books, and research reports. The research results show that a collaborative, adaptive, and participatory organizational culture is very important for driving the success of the Merdeka curriculum, which can be achieved through transformational leadership strategies, collaborative supervision, and school autonomy to create an innovative and autonomous work environment that aligns with the Merdeka curriculum.